ByzRev 07.2025.030: Mark Roosien, Ritual and Earthquakes in Constantinople:: Liturgy, Ecology, and Empire. Cambridge: Cambridge University Press 2024. - Mellas, Andrew (The Byzantine Review, 2025)
Mark Roosien, Ritual and Earthquakes in Constantinople: Liturgy, Ecology, and Empire. Cambridge: Cambridge University Press 2024. 204 pp. – ISBN 978-1-009-42728-9